2019
DOI: 10.1007/s13300-019-00708-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Sodium Glucose Co-Transporter-2 Inhibitors in Japanese Patients with Diabetes Mellitus

Abstract: IntroductionSodium glucose co-transporter-2 inhibitors (SGLT2i) have been on the market for 5 years in Japan. We explored the real-world effectiveness of SGLT2i in Japan.MethodsWe retrospectively analyzed two large Japanese administrative databases from JMDC Inc.: insurance-dataset (I-dataset) and Medical Data Vision Co. Ltd. [hospital-dataset (H-dataset)]. Patients who newly started SGLT2i or other oral antidiabetic drugs (OADs) between 1 April 2014 and 31 March 2016 were selected for this analysis and follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…29 While 24% of T2DM patients achieved the target HbA1c (≤7%) in our study, the same was achieved by 19.6-22.6% of Japanese patients with the use of other SGLT2i at 12 months, and by 26.5% of patients in a retrospective, real-world, observational study in T2DM patients in Thailand over 16 months follow-up. 30,31 Likewise HbA1c, statistically significant improvements were observed with FPG (52.3 mg/dl) and PPG (103.6 mg/dl) in our study. These improvements were much higher than that reported by Dharmalingam et al at week 24 with remogliflozin 100 mg (17.86 mg/dl and 39.2 mg/dl).…”
Section: Discussionsupporting
confidence: 63%
“…29 While 24% of T2DM patients achieved the target HbA1c (≤7%) in our study, the same was achieved by 19.6-22.6% of Japanese patients with the use of other SGLT2i at 12 months, and by 26.5% of patients in a retrospective, real-world, observational study in T2DM patients in Thailand over 16 months follow-up. 30,31 Likewise HbA1c, statistically significant improvements were observed with FPG (52.3 mg/dl) and PPG (103.6 mg/dl) in our study. These improvements were much higher than that reported by Dharmalingam et al at week 24 with remogliflozin 100 mg (17.86 mg/dl and 39.2 mg/dl).…”
Section: Discussionsupporting
confidence: 63%
“…In a large nation‐wide Canadian cohort study by Brown et al, 1520 patients were analysed 3 to 6 months after dapagliflozin initiation and demonstrated a mean HbA1c reduction of 0.9%, mean weight reduction of 2.2 kg and drop in systolic blood pressure by 3.7 mm Hg—effects that are largely aligned with the magnitude of effects reported in clinical trials . Ito et al conducted a larger cohort study involving just over 150 000 T2D patients treated with an oral anti‐hyperglycaemic agent followed for 1 year . SGLT2 inhibitor use was associated with improvements in HbA1c levels from baseline at levels comparable to other agents.…”
Section: Kidney Protection In Cvotsmentioning
confidence: 87%
“…The average PDC of SGLT2 inhibitors at one year was between 0.64 and 0.79 [ 41 , 42 ]. Likewise, the proportion of patients who continued to take SGLT2 inhibitors at one year ranged between 44.3 and 72.1% [ 42 , 43 ].…”
Section: Sodium Glucose Co-transporter-2 Inhibitorsmentioning
confidence: 99%